Observing microstructural evolution during plaster hydration - Song, Kyung-Min; Mitchell, Jonathan; Gladden, Lynn F. (Diffusion Fundamentals, 2009)
Calcium sulphate hemihydrate (CaSO4·0.5H2O), commonly known as plaster of Paris, is used extensively in the construction, ceramics, and medical industries. There are two varieties of plaster referred to as α and β, produced by “wet” or “dry” methods respectively. Plaster hydrates to form crystalline gypsum (CaSO4·2H2O, dihydrate). We present a comparative in situ study of the microstructural changes that occur during the hydration of the two forms of plaster at a water-to-plaster ratio of w/p = 0.8 using NMR relaxometry and electron microscopy. In the α-plaster, pores evolve gradually to form a uniform, interconnected structure. In contrast, the β-plaster hydrates faster, leading to a less homogeneous product with micro-cracks resulting from rapid chemical shrinkage.